2012
DOI: 10.1029/2012gl051788
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wind waves on the development of river mouth bars

Abstract: [1] River deltas are among the most important environments on earth, housing productive ecosystems and a large fraction of the human population. The key process for delta development is the deposition of mouth bars in front of delta distributaries. Predicting mouth bar formation on marine coastlines is complex because of the interactions between waves, tides, water and sediment discharge. Here we study the effects of waves on mouth bar growth with the coupled sediment transport and wave model Delft3D-SWAN. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 17 publications
7
62
0
1
Order By: Relevance
“…The transition from ZOFE to ZOEF marks the downstream location at which the turbulence generated by shearing along the margins of the jet affects the entire jet [Bates, 1953]. Jet theory has been largely used to describe rivers and inlets discharging into a standing water body [Bates, 1953;Wright and Coleman, 1974;€ Ozsoy and € Unl€ uata, 1982;Wright, 1977;Rowland et al, 2010;Falcini and Jerolmack, 2010;Nardin and Fagherazzi 2012;Nardin et al, 2013].…”
Section: Hydrodynamic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition from ZOFE to ZOEF marks the downstream location at which the turbulence generated by shearing along the margins of the jet affects the entire jet [Bates, 1953]. Jet theory has been largely used to describe rivers and inlets discharging into a standing water body [Bates, 1953;Wright and Coleman, 1974;€ Ozsoy and € Unl€ uata, 1982;Wright, 1977;Rowland et al, 2010;Falcini and Jerolmack, 2010;Nardin and Fagherazzi 2012;Nardin et al, 2013].…”
Section: Hydrodynamic Resultsmentioning
confidence: 99%
“…[3] Researchers have analyzed both large-scale structure of deltaic systems [Edmonds, 2012b;Edmonds et al, 2009Edmonds et al, , 2011aEdmonds et al, , 2011bEdmonds and Slingerland, 2010;Canestrelli et al, 2010, Geleynse et al, 2010, 2011Jerolmack, 2009;Jerolmack and Paola, 2007;Fagherazzi, 2008;Jerolmack and Swenson, 2007;Fagherazzi and Overeem, 2007] and their morphological units, such as mouth bars [Esposito et al, 2013;Nardin et al, 2013;Nardin and Fagherazzi, 2012;Edmonds and Slingerland, 2007;Wang, 1984;Wright, 1977;Bates, 1953].…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study Nardin and Fagherazzi [] showed that waves and the direction from which they approach a river mouth play an important role in the distribution of sediments and related deposits. In a series of numerical experiments carried out with the model Delft3D coupled with SWAN waves affect bar development in two ways: by modifying the direction of the river jet and by changing the bottom shear stress at the river mouth and hence increasing jet spreading.…”
Section: Wave Influence On River Mouth Depositsmentioning
confidence: 99%
“…By construction, the matrix M is upper triangular, with ones on the main diagonal for the first (|V| -k) rows and with the last k rows being zero. Using the rank-nullity theorem [Meyer, 2000], dim(ker(M)) 5 k.…”
Section: Appendix A: Finding the Number Of Alternative Paths To An Oumentioning
confidence: 99%